Circular RNA Circ-03955 Promotes Epithelial-Mesenchymal Transition in Osteosarcoma by Regulating miR-3662/Metadherin Pathway - Wang, Zhengguang; Deng, Mingsi; Chen, Liangjian; Wang, Weiguo; Liu, Gengyan; Liu, Dongbiao; Han, Zhipeng; Zhou, Yong (Frontiers in Oncology, 2020)
Osteosarcoma is the most common primary malignant tumor, especially in children and adolescents. Circular RNAs (circRNAs) are found to play roles in the progression of osteosarcoma. However, the exact functions of circRNAs in osteosarcoma development still need to be clarified. We obtained differentially expressed circRNAs and miRNAs from a GSE99671 data set (GEO database). The gene co-expression network of ceRNAs and osteosarcoma-related genes was analyzed using the STRING database. qRT-PCR was used to detect the expression of circ-03955 and miR-3662. Transwell assays and flow cytometry were performed to detect phenotypic changes in cell function. A xenograft tumor model was established using BALB/c nude mice. Dual luciferase activity and RNA immunoprecipitation assays were performed to assess the relationship between circ-03955, miR-3662, and metadherin (MTDH). Immunohistochemistry, immunofluorescence, and Western blotting were used to assess protein expression levels. Circ-03955 was significantly upregulated, and miR-3662 was downregulated in osteosarcoma. Circ-03955 silencing inhibited the growth and metastasis of osteosarcoma. Mechanism analysis revealed that circ-03955 could bind to miR-3662, and the latter could target MTDH, leading to its suppressed expression and facilitating epithelial-mesenchymal transition (EMT). All these findings demonstrate that the presence of circ-03955 promotes EMT in osteosarcoma by acting as miR-3662 sponge-mediated MTDH expression.